A review of the literature on big data in marketing using text mining - Amado, Maria Alexandra Amorim (2016)
With the amount of currently existing data, organizations have access to more information, collecting data of all kinds and accumulating easily terabytes or petabytes of data. These data come from various sources: streams of social networks, mobile, pictures, transactions, GPS signals and more. To analyze this large amount of data currently designated as Big Data, it is increasingly a concern of organizations in terms of competition, enhancing productivity growth and innovation. But what exactly is Big Data? The Big Data is more than just a matter of size: with the emergence of new technologies for data collection and advanced data mining, through powerful data analysis tools, Big Data offers an unprecedented opportunity to acquire knowledge with new types of data and discover business opportunities faster. Its application to Marketing can bring great potential to organizations allowing a better view of the market, creation of better consumer interactions through research of their behavior, in order to identify what the right message to deliver at the right channel, at the right time to the right consumer. These improved interactions result in increased revenues and competitive differentiation. Text Mining was used in this study to develop an automatic literature review and analyze the application of Big Data in Marketing in four dimensions: Temporal, Geographic, Sectors and Products.